(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The study aimed to investigate the prevalence of Enteroaggregative E.coli obtained from children of Thi-qar suffered from diarrhea through PCR detection of virulence factors (aggR, astA, pic) antibiotic resistance and extended spectrum ?-lactamase (ESBL) production. The investigation included collection 430 stool samples from diarrheic children under five years involved both gender and 40 samples as a control from healthy children , were consulted in (Bint al- Huda Hospital for Gynecology obstetrics and pediatrics , Al-Mousawi hospital and private clinics laboratory ) at a period extended from 10th December 2018 -21th July 2019. A total of the isolates were diagnosed by different laboratory and molecular method. PCR diagnosis confirmed the distribution of genes (aggR and astA) within EAEC were (66% and 53%), respectively. The highest resistance to antibiotics was (100%) to ceftazidime and cefpodoxime , (97% ) to ceftriaxone, followed by (96%) for Ampicillin, Sulfa-Trimethoprim and cefuroxime, respectively, and cefixime, amoxiclav, Cefotaxim and Tetracycline (94.8%), (92.3%), (85%) and (78.2%), respectively. While the medium resistance was (55.13%) for each of ciprofloxacin , piperacillin-tazobactam, respectively, and Amikacin (51%). While the lowest resistance was to Gentamicin (30.7%) and Imipenem (26.9%). EAEC isolates were multidrug resistance in average 64/66 (96.97%).